NON-SPECIFIC PROTECTION FACTORS AND INFLAMMATORY MEDIATORS IN URINE OF CHILDREN WITH GLOMERULONEPHRITIS IN THE PRESENCE OF HERPESVIRAL INFECTION NOTICE 2. DETERMINATION OF THE LEVEL OF IL-8 AND SLPI - I. Bagdasarova; I. Kruglikova; E. Kornilina; V. Kruglikov (Ukrainian Journal of Nephrology and Dialysis, 2016)
The aim of this work was the study of indicators characterizing the local immunity in patients with various forms of glomerulonephritis by presence of herpesviral infection.Materials and methods. A quantitative estimation of the content of IL-8 and SLPI in urine of 47 patients with glomerulonephritis and 10 apparently healthy individuals was conducted.Results. A insignificant increase of IL-8 level in urine was showed in patients with glomerulonephritis. The level of urinary SLPI was reliably higher than the control value, at the same time the majority ofpatients (74,0 %) did not exceed the upper limit of the physiological norm. The essential increase ofIL-8 level in urine was observed in 13 sick children, and of SLPI – in 12 patients. The increase of IL-8 and SLPI levels was observed more frequently in patients with hematuric form of glomerulonephritis, with nephrotic steroidoresistant variant of nephrotic form, in the absence of remission, and in the case of IL-8 - with severe course of the disease. More such changes were found in children with active (reactivated) herpesviral infections.Conclusion. There has been confirmed the importance of the study of immunologic parameters in the urine of patients with glomerulonephritis to characterize immunopathological process in the kidney and prognosis of the disease.